Static test study on precast concrete frame beams with large-diameter and high-strength steel bars. Issue 1 (March 2020) - Zhang, Y; Shi, B; Jin, L; Liu, M
Abstract: The paper is focused on the mechanical properties of precast concrete frame beams with large-diameter and high-strength steel bars. The full-scale static tests and nonlinear finite element analysis were carried out on the two proposed beams with steel bars of HRB500 Ø32-Ø25 and Ø40-Ø32 to study the load-carrying capacity, flexural capacity and plastic rotational capacity. The influence of steel bar diameter on mechanical properties were explored. On the basis of equal-strength principle of flexural capacity at the same time, the finite element model of the cast-in-place concrete frame beam with large-diameter of HRB500 and ordinary steel bars of HRB400 were compared. Results indicated the properties of the precast concrete frame beams with large-diameter and high-strength steel bar. The load-carrying capacity of the prefabricated concrete beam with steel bars of Ø40-Ø32 was higher. The coefficient of plastic rotational capacity was 3.41 and 2.88 of specimens with steel bars of HRB500 Ø32-Ø25 and Ø40-Ø32, respectively. The positive section yield bending moment could be calculated by the current concrete codes. The properties such as yield load, flexural bearing capacity and the plastic rotational capacity were similar to the cast-in-place concrete frame beam, and could be verified by the current standard.